How effective is emissions pricing? The role of firm-product-level adjustment - Karin Mayr (Johannes Kepler University of Linz, Department of Economics, 2024)
Climate change is one of the pressing issues of our time, and carbon emissions caused by industrial production are among its most important drivers. This paper analyses how multi-product firms adjust to an increase in the cost of emissions (e.g. due to the introduction of emissions pricing) in terms of their output, product mix, and technology, and how their emissions change in response, depending on firm-specific production patterns and cost structures. My model delivers a (qualitative and quantitative) assessment of changes in aggregate emissions via conventional margins of firm adjustment that have not been sufficiently studied in the literature so far. In numerical simulations, I find that negative effects of emissions pricing on emissions of multi-product firms can be sizeable.
Keywords: Q54; Q56; D24; 330; emissions; carbon tax; multi-product firms; product mix; technology